Math Questions and Answers

Start Your Free Trial

Given f(x) and g(x), please find (fog)(X) and (gof)(x) f(x) = 2x   g(x) = x+3   

(fog)(x) = 2x + 6

(gof)(x) = 2x + 3

Expert Answers info

hala718 eNotes educator | Certified Educator

calendarEducator since 2008

write3,662 answers

starTop subjects are Math, Science, and Social Sciences

f(x) = 2x

g(x) = x + 3

First let us find (fog)(x)

(fog)(x) = f(g(x)

             = f(x+3)

               = 2(x+3)

               = 2x + 6

==> (fog)(x) = 2x + 6

Now let us find (gof)(x):

(gof)(x) = g(f(x)

            = g(2x)

           = 2x + 3

==> (gof)(x) = 2x + 3

check Approved by eNotes Editorial

lovespacetech | Student

We have given f(x) = 2x and g(x) = x+3

We have to find, (fog)(x) = f(g(x)) and (gof)(x) = g(f(x))

1. For finding (fog)(x) = f(g(x)), we have to replace x by g(x) in f(x)

So, (fog)(x) = f(g(x)) = 2*g(x) = 2*(x+3) = 2x+6

2. For finding (gof)(x) = g(f(x)), we have to replace x by f(x) in g(x)

So, (gof)(x) = g(f(x)) = f(x)+3 = 2x+3

So, finally (fog)(x) = 2x+6

(gof)(x) = 2x+3

tiuhinmaji314 | Student

Here f(x) and g(x) is defined .We are asked to compute the composition functions (fog)(x) and (gof)(x).

Now (fog)(x)





Also (gof)(x)




This image has been Flagged as inappropriate Click to unflag
Image (1 of 1)
kalwanaski87 | Student

I like to write composition problems such as this one as g(f(x)) and f(g(x)) rather than the (fog)(x) and (gof)(x). I do this because it reminds me the order in which to solve the problem. When we are finding g(f(x)), I want to work inside out. This means since f(x) is the inner most part of the equation, I want to take f(x) and plug it into g(x), as shown below:

g(f(x)) = g(2x) <---- I replaced the f(x) with 2x because they are equal

In the g(x) equation, we need to replace the x with 2x, so:

g(2x) = 2x + 3

There is nothing to simplify in the above equation, so we now know that g(f(x)) = 2x + 3

The process is similar for f(g(x)).

f(g(x)) = f(x+3) <------ Again, working inside out.....g(x) is replaced with x + 3 because they are equal.

f(x +3) = 2(x + 3) <------x in the f(x) equation is replaced with x + 3

= 2x + 6 < ----- distributing the 2 to the x and the 3 gets the final answer

so f(g(x)) = 2x + 6

rimmery | Student

So remember that `(f@g)(x)=f(g(x))`

so subbing in g(x), we get


Replacing each x in f with x+3, we get




For `(g@f)(x)=g(f(x))`

We have that `(g@f)(x)=g(f(x))`



giorgiana1976 | Student

To calculate the compositions of the functions, we'll apply the rule:

(fog)(x) = f(g(x)) (f of g of x)

It is obvious that we'll substitute x by the expression of g(x) and we'll get:

f(g(x)) = f(x+3) = 2*(x+3)

We'll remove the brackets and we'll have:

(fog)(x) = 2x + 6

Now, we'll calculate  (gof)(x).

 (gof)(x) = g(f(x)) (g of f of x)

It is obvious that we'll substitute x by the expression of f(x) and we'll get:

g(f(x)) = g(2x) = 2x + 3

(gof)(x) = 2x + 3

neela | Student

f(x) = 2x. g(x) = x+3.

To find (fog)(x) and (gof)(x).


f(x) = 2x. g(x) = x+3.

Substitute g(x) for x in f(x) to get (fOg)(x): 

f((g(x)) = 2 (g(x) = 2(x+3) = 2x+6.

To get (gof)(x), substitute  f(x) for x in g(x):

(gof)(x) =  (2x) + 3 = 2x+3.